Anti-inflammatory effects and molecular mechanisms of bioactive small molecule garlic polysaccharide - Shao, Xin; Li, Jialong; Zhang, Huidan; Zhang, Xuhui; Sun, Chongzhen; Ouyang, Xin; Wang, Yong; Wu, Xiyang; Chen, Chunbo (Frontiers in Nutrition, 2023)
Although garlic polysaccharides have been found to possess anti-inflammatory activities, anti-inflammatory study on small molecule water-soluble garlic polysaccharide (WSGP) is few. In this study, a novel WSGP with a molecular weight of 1853 Da used to be isolated and the chemical composition was identified. WSGP showed strong antioxidant activity, such as DPPH, hydroxyl, superoxide anion, ABTS radical scavenging capacity, Fe2+ chelating ability and reducing power. Meanwhile, WSGP ought to considerably suppress the manufacturing of NO and the mRNA and protein expression degrees of IL-6, TNF-α, and IL-1β in LPS inspired RAW264.7 macrophages WSGP could significantly suppress the production of NO and the mRNA and protein expression levels of IL-1β, IL-6, and TNF-α in LPS stimulated RAW264.7 macrophage cells (p < 0.05). In addition, the phosphorylated IκB-α, p65, and STAT3 proteins were significantly increased in LPS-induced macrophages, while this trend was significantly reversed by WSGP treatment in a concentration-dependent manner (p < 0.05). Consequently, WSGP supplementation might reduce LPS-induced inflammatory responses by suppressing proinflammatory cytokines and NF-κB and STAT3 pathway activation. The finding of this research would give scientific guidelines for the judicious use of small molecular garlic polysaccharide in anti-inflammatory treatments.